Analisis Biaya Kontribusi dalam Pengelolaan Ekowisata Bahari Berkelanjutan di Kota Kendari - Riska Raisu; Eliyanti Agus Mokodompit (Yayasan Cendekia Gagayunan Indonesia, 2026)
Sustainable marine ecotourism management requires effective financing planning to maintain the sustainability of coastal ecosystems while improving the quality of tourism services. This study aims to analyze the role of contribution costs incurred by various stakeholders, including local governments, tourist destination managers, and local communities, in supporting sustainable marine ecotourism management in Kendari City. This research uses a qualitative approach with a literature study method, by examining various relevant scientific sources related to the concept of ecotourism, sustainable development, and contribution cost mechanisms in coastal natural resource management. Data was collected through a search of scientific journals, policy reports, and other supporting documents, then analyzed in a descriptive-analytical manner to identify cost allocation patterns and their impact on ecotourism sustainability. The results of the study show that contribution costs allocated in a structured and transparent manner play an important role in strengthening environmental conservation efforts, increasing the attractiveness of tourist destinations, and encouraging the active participation of local communities in preserving marine ecosystems. In addition, multi-stakeholder involvement in ecotourism management financing has been proven to improve management effectiveness and long-term sustainability. This study confirms that proper planning and management of contribution costs is an important foundation in the formulation of sustainable marine ecotourism policies in Kendari City. Therefore, this study recommends the need for the preparation of an integrated, accountable, and participatory contribution fee scheme as the basis for strengthening sustainable marine ecotourism management policies.